Intertextuality in the Poem of Sheikh Abdul Salam Al-Murtawi Al-Barnawi - Muhammad Tijjani Muhammad (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
Intertextuality is contraction and crowding. In this sense, it is close to the meaning of intertextuality in its modern concept, which refers to the overlap of texts. The introduction to this research comes with a study of how and what kind of library study is conducting research in libraries through reading, studying and taking notes on different literatures or reading materials that match the topic, then filtering them and showing them in the theoretical framework. The data sources come from the primary source and the method of collecting its data is carried out using documentation techniques. The method of analyzing its data depends on content analysis or content study. It became clear from this that the poet used the language of imagery, so he represented meanings and personified them, so he brought the distant closer, clarified the mysterious and facilitated the difficult meanings, which testifies to the magnificence of his poetic language